INSECTICIDAL EFFICACY OF AQUEOUS EXTRACTS OF Ricinus communis, Baccharis trimera AND Chenopodium ambrosioides ON ADULTS OF Alphitobius diaperinus - CHARLIE-SILVA, I.; SOUZA, L. M.; PEREIRA, C. C.; MAZZONETTO, F.; BELO, M. A. A. (Ars Veterinaria, 2019)
Seeking alternative strategies for health management to control mealworm in poultry barns, in vitro study evaluated the insecticide effect of Ricinus communis, Baccharis trimera and Chenopodium ambrosioides extracts against adults of Alphitobius diaperinus. The extracts were tested at concentrations of 0, 2, 4 and 8%. To study insecticidal effects was designed an experiment containing groups with 20 adults in 3 replicates for each treatment, evaluating the mortality percentage of 1, 3, 16 and 24 hours after treatment with counting of live and dead adults. Greater insecticidal effect was observed in treated mealworm with 8 % of R. communis aqueous extract (59.0%) compared to C. ambrosioides and B. trimera which had percentages of mortality of 44.6% and 0.0% at the same concentration, respectively. The aqueous extracts of R. communis and C. ambrosioides at 8% showed promising results for the control of adults mealworm. However, pharmacological studies must be designed to determine strategies and formulations for viable application of these extracts in poultry facilities, as well as to determinate the formulations stability, clinical and environmental safety treatments.